Transitions to Professional Education in Switzerland: The Influence of Institutional Characteristics of the Swiss VET System - Sander Fabian; Kriesi Irene (Swiss Journal of Sociology, 2021)
Based on human capital and institutional theory, this article investigates whether transitions into professional education depend on institutional characteristics of the preceding initial vocational education and training program. The empirical analyses make use of the SLFS data. They show that vertically nondifferentiated initial vocational education and training programs with high shares of vocational school and standardized final exams increase the probability to enter professional education.